(untitled) (Indian Journal of Physiotherapy and Occupational Therapy - An International Journal, 2026)
The International Classficiation of Functioning, Disability and Health (ICF) developed by WHO, offer a standardized, biopsychosocial framework to assess health and functioning. Its Pediatric version International Classification of Functioning ,Disabilty and Health for Children and Youth( ICF-CY), addresses developmental aspects specifics to children. Although it aids clinical descision-making and outcome evaluation in pediatric physiotherapy, its integration into routine clinical practise is still not widespread .This limited adoption may be due to factors such as lack of awareness, training and percieved complexity in applying the framewrok in everyday practice. The objective of the study is to asses the level of knowlwdge and utilization of International Classification of Functioning, Disability and Health (ICF) among pediatric physiotherapists. Method: A cross sectional study was conducted among 95 pediatric physiotherapists practising in Bangalore, Karnataka. Participants were selected based on inclusion and exclusion criteria using purposive sampling. A structured questionnaire was used to asses knowlwdge and utilization of the ICF. Conclusion: Among 95 pediatric physiotherapists surveyed, 55.8% demonstrated average knowledge of the ICF, 27.4% had good knowledge and 16.8% were below aveage. The study highlights the pediatric physiotherapists have average knowledge of the ICF, with limited good understanding and a notable portion showing below average knowledge.These findings emphasize the need for enhanced training to improve ICF use in clinical practise and support better patient outcome